2005
DOI: 10.2519/jospt.2005.35.12.793
|View full text |Cite
|
Sign up to set email alerts
|

Strength Around the Hip and Flexibility of Soft Tissues in Individuals With and Without Patellofemoral Pain Syndrome

Abstract: Study Design: Case control design. Objectives: To investigate whether differences exist in lower extremity muscle strength and soft tissue length between patients with patellofemoral pain syndrome (PFPS) and age-and gendermatched control subjects. Background: Based on our clinical experience and emerging data, impairments such as muscular weakness surrounding the hip and limited flexibility of key lower extremity muscles may be important impairments to consider in the conservative management of PFPS. Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
207
4
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(229 citation statements)
references
References 32 publications
6
207
4
12
Order By: Relevance
“…These were labeled A and B by figure 1 -Flow diagram for study design. on the quadriceps muscle at 60° of knee flexion (20) , 11-point visual numerical pain scale (VNPS) (21) and Lequesne algofunctional questionnaire (22) . The VNPS consisted of a ruler divided into 11 equal parts numbered from 0 to 10, in which 0 corresponded to "no pain" and 10 corresponded to the "worst pain imaginable".…”
Section: Methodsmentioning
confidence: 99%
“…These were labeled A and B by figure 1 -Flow diagram for study design. on the quadriceps muscle at 60° of knee flexion (20) , 11-point visual numerical pain scale (VNPS) (21) and Lequesne algofunctional questionnaire (22) . The VNPS consisted of a ruler divided into 11 equal parts numbered from 0 to 10, in which 0 corresponded to "no pain" and 10 corresponded to the "worst pain imaginable".…”
Section: Methodsmentioning
confidence: 99%
“…4,17,29 In spite of the fact that intervention programs for the management of patients with PFPS include exercises aimed at improving the performance of the lateral hip musculature, we are aware of only 2 research reports that have investigated whether differences in hip strength exist between patients with PFPS and a control group. 12,20 Ireland et al 12 found that 15 female subjects with PFPS demonstrated 26% less hip abduction strength and 36% less hip external rotation strength when compared to 15 age-matched control subjects. In contrast, Piva et al 20 reported that there were no statistically significant differences in hip abduction or external rotation strength when 30 subjects with PFPS (17 females and 13 males) were compared with 30 age-and gender-matched control subjects.…”
Section: 726mentioning
confidence: 99%
“…12,20 Ireland et al 12 found that 15 female subjects with PFPS demonstrated 26% less hip abduction strength and 36% less hip external rotation strength when compared to 15 age-matched control subjects. In contrast, Piva et al 20 reported that there were no statistically significant differences in hip abduction or external rotation strength when 30 subjects with PFPS (17 females and 13 males) were compared with 30 age-and gender-matched control subjects. Different methods for stabilizing the dynamometer and different positions for testing hip external rotation strength may account for these conflicting results.…”
Section: 726mentioning
confidence: 99%
“…33 Each patient performed knee flexion or extension for 5 repetitions as a warm up prior to the test. The maximal isometric muscle strength of knee flexor and extensor of the tested limb were measured for three trials.…”
Section: Isometric Muscle Strengthmentioning
confidence: 99%
“…The maximal isometric strength appeared automatically on the dynamometer screen. 33 Mean values of three trials were calculated for each patient.…”
Section: Isometric Muscle Strengthmentioning
confidence: 99%